POTENSI SARAMBU MARURUN SEBAGAI DAYA TARIK WISATA ALTERNATIF DI TORAJA UTARA - Hardianti Hardianti; Meidy Putri Utami; Faris Jumawan (Program Studi S1 Pariwisata, Universitas Muhammadiyah Gorontalo, 2024)
This study aims to explore the potential and problems of Sarambu Marurun tourist attraction in Awan Rantekarua District, North Toraja, South Sulawesi, to identify appropriate development strategies. The method used is a qualitative approach, through field observations, in-depth interviews with stakeholders, and documentation. The data was analyzed based on the concept of Attractions, Accessibility, and Amenities (3A). The results of the study show that Sarambu Marurun has great potential as a tourist destination with a unique natural attraction in the form of a two-tiered waterfall, but its management is still minimal. The available facilities are limited, accessibility to the location is inadequate, and the promotion of this attraction is not optimal. This study recommends improving infrastructure such as improving road access, adding supporting facilities, and developing ecotourism concepts that involve the participation of local communities that have been made in the form of site signs or travel patterns that are expected to provide a development concept that in the future can increase tourist visits while preserving the environment and local culture, making Sarambu Marurun an alternative tourist destination in Toraja North.